Aquarela sustentável: uma análise fenomenográfica sobre sustentabilidade, com uso de materiais visuais, numa organização escolar paraibana - Santos, Helaine Cristine Carneiro dos (2017)
The sustainability speech has been one of the most discussed topics in recent decades. Its gradual expansion has influenced several fields of know ledge, among which the field of education, a fundamental element in all processes of the constitution of citizenship. For this reason, to contribute to the expansion of the discussions about this theme and the actions directed to education for sustainability, this work aims, through the phenomenological approach, to analyze the conceptions of sustainability for the II Elementary School students in a school organization. The epistemological position used in this research was interpretative, qualitative. Both approaches are consistent with the phenomenological method used in this study. The application of this research in primary education is justified by the fact that this period has a larger number of enrolled children and adolescents taking an average of 9 years to complete. In addition, the choice for the II Elementary School was due to the fact that children and adolescents internalize the meanings and values of the world but also because they contribute to their establishment and modification, (re)producing and (re)creating individual and collective behaviors that will accompany them throughout their lives. Five sustainability conceptions of the II Elementary School students were identified: sustainability concepts with a focus on the individual; sustainability concepts focused on the local lived context; sustainability concepts with a focus on the global context, conceptions idealizing and transformative sustainability conceptions, being classified from the most superficial to the deepest, respectively. The research revealed that most of the students who participated in the research conceptualize sustainability by relating it to their local lived context, category II. Observing the variation of these conceptions during elementary school, it is noticed that, for the most part, students' conceptions are still superficial. In addition, this work sought to provide theoretical-empirical contributions on the meaning of sustainability, based on the results, with suggestions for improvements in the process of insertion of sustainability education into the school environment, using the students' own perception of the theme. Thus, five suggestions were scored: the creation, in the school environment, of an organic garden, maintained by the students themselves; development of programs aimed at planting trees in the community; more actions aimed at the rational use of water and electricity; placing in the school containers intended for the disposal of spent batteries and accumulators; and use of an application that replaces printed school notices. This result points out that the path is still long, but it is already beginning to be tackled and that only through education for sustainability can these children and adolescents change their reality.